The New Testament. A Philological Overview - Piñero, Antonio (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2018)
Independent philological University research in Spain should commit to New Testament and early Christianity studies. The reason for this is that the New Testament was conceived and written in Koine classical Greek. Because of this it belongs by its own right, to the imperial Greek literature. No other book composed in this language has had such a dissemination and impact as the New Testament, the theoretical bedside book for more than two thousand million people. The confessional research on the New Testament has its own limits, but the independent approach that can be accomplished at University has no more barriers than the use of sound, rational, historical and critical methodology typical of the philological work. This article defends twelve theses summarizing an overview of the New Testament from the point of view of Classical Philology. These help to understand what actually this corpus means and they encourage to study it from a historical, philological point of view that does not involve the concept of divine inspiration. This does not mean to deny it, but does not take it into consideration.
Keywords: New Testament; Koine Greek; Ancient Christianity language and literature; Methodology of non-confessional religious research.